Histological study of hamster buccal mucosa following topical application of DMBA and exposition to low power 337 nm laser light - De Barros Rego, C. M V; Munin, E.; Redígolo, M. L.; Salgado, M. C. [UNESP]; De Souza, H. P.; Colombo, C. E D; Nicolau, R. A.; Alves, L. P.; Zângaro, R. A. (SPIE, the international society for optics and photonics, 2003)
The aim of the present work is to analyze the histological changes on hamster buccal mucosa caused by the topical use of 7,12-dimethylbenzanthracene (DMBA) and exposition to a 220 μJ/pulse nitrogen laser light (@ 337 nm) at an average power of 2,3 mW. Twenty-one hamsters divided into two experimental groups were treated six times with DMBA. One hamster was kept as control. Group I was composed by ten hamsters and was submitted only to DMBA. Group II, also with ten hamsters, received the same treatment as group I and was exposed to the laser radiation. The time duration of each irradiation section was 10 seconds. All the treatment happened in alternated days. The histological analysis took place twice, after the end of the treatment and after sixty days. Both experimental groups presented dilatation of vessels, thickening of the epithelial tissue and the presence of inflammatory infiltrates. The preliminary results indicates that in group II the number of dilated vessels and its new area are much more significant than in group I.
Keywords: Carcinogenesis; DMBA; Mutagenesis; UV laser; Carcinogens; Irradiation; Lasers; Ultraviolet radiation; Hamster buccal mucosa; Histology